Value Analysis of Passenger Car Equivalent Motorcycle (Case Study Kartini Road Bandar Lampung) - Juniardi JUNIARDI; Aflah Efendi (Bandar Lampung University (UBL), 2013)
Motorcycles in traffic mix on the 4 lane one-way road with no median dividers berpootensi an impact on the performance of the particular traffic volume of traffic, especially if the number of vehicles is very large motorcycle. This happens in the corridors of Bandar Lampung particularly traffic from the south or from the Gulf Betung.Studi done in the way of Kartini Bandar Lampung, ie after Kartini Mall and right in front lembga technocrat education. Survey conducted on Tuesday and Wednesday morning at peak hour, peak hour lunch, and afternoon peak hours by using a video camera. Results of analysis of the proportion of motorcycles acquired: On Tuesday, at 67.91% of the total volume of traffic, and Wednesdays at 69.73% of the total traffic volume, so that the average proportion was 68.82%, which shows that the growth of motorcycle high enough , the average value exceeds the normal composition according MKJI 1997 is 38%. Due to the growth of the motorcycle vehicle large enough for the volume of traffic, it is necessary to review the value of PCE for motorcycles as part of the traffic. Analysis is used to determine the value of PCE is to use the base capacity. The capacity of the base using multiple linear regression model. The results of the analysis obtained niali emp for motorcycles on the road Kartini is emp MC = 0.564, and emp HV = 1.347. Recommended for 4 lane road with no median one-way lane that has not been facilitated by special motor bike, then you should apply the separation column in order to reduce the level of accidents and provide security and comfort for pedestrians to cross the road.